Multimedia transcoding in mobile and wireless networks - Ahmad, Ashraf M. A.; Ibrahim, Ismail Khalil (Gale virtual reference library, 2009)
Provides readers with relevant theoretical frameworks and latest technical and institutional solutions for transcoding multimedia in mobile and wireless networks. Addresses the transcoding of all multimedia elements including video, audio and text, while addressing both practical and theoretical problems in the field.